Cultivation of Goji (Lycium Barbarum) Plant on Irrigated Gray and Meadow Soils - Eminjonovna, Djurayeva Dilrabo (American Journal of Botany and Bioengineering, 2026)
This article provides a detailed study of the cultivation of goji (Lycium barbarum) under irrigated conditions on gray and meadow soils in Uzbekistan. Attention is given to the climatic and soil requirements of the goji plant, and scientifically based recommendations are provided regarding irrigation regimes, soil preparation, seed selection, fertilization, and care methods. Additionally, information is presented on the advantages of growing goji on gray and meadow soils, harvesting technologies, as well as measures for controlling diseases and pests. The research results demonstrate the potential for successful development of goji cultivation in Uzbekistan and can be applied in the development of agronomically and economically efficient technologies in this field. The article serves as a valuable resource for agricultural specialists, researchers, and producers.